Family Forest Ownerships Trends in the United States, 2013–2023: Results from the USDA Forest Service, National Woodland Owner Survey - Brett J. Butler (Journal of Forestry, 2026)

Efficacy, non-target impacts, and costs of mechanical control options against a bioturbator in bivalve aquaculture - Jennifer L. Ruesink; C. Haleh Mawson; Brian Allen; Jeffrey Barrett; David Beugli; Steven Booth; Laura Butler; Bill Dewey; Cinde R. Donoghue; Brett R. Dumbauld; Kristine Feldman; Zachary Forster; et al. (Aquaculture, 2025)

Spatial variability in water strontium isotopes and trace metals from the Clarence River Basin, New South Wales, Australia - Lauren J. Stoot; Lee J. Baumgartner; Gavin L. Butler; Jason D. Thiem; Brett M. Knowles; Gregory S. Doran (Hydrobiologia, 2024)
Understanding fish movement in river systems is essential in identifying habitats which are important for species to perpetuate. Water chemistry, paired with fish otoliths, can be used to trace movements among different habitats, although a detailed understanding of spatial variation in water chemistry is first required. To obtain this knowledge, we analysed surface water collected from 59 sites throughout the Clarence River Basin, a coastal river basin in northern New South Wales, Australia. The primary objective was to quantify the spatial variation of trace metals and strontium isotope ratios ( 87 Sr: 86 Sr) for future and paired use with otolith microchemistry to track fish movement. Using ICP-OES, we identified that some trace metals, particularly strontium and barium as well as 87 Sr: 86 Sr ratios, varied spatially when analysing all water samples and revealed three distinct regions centring around the estuary, interior and outer regions. These differences were driven by variation in the underlying surface geology between the Clarence–Moreton Basin and the New England Block. Tidal influence also affected trace metals and 87 Sr: 86 Sr ratios throughout the estuarine area. We suggest that the level of differentiation identified in the current study has the potential to discriminate broad-scale fish movements among regions/habitats using otolith analysis, with fine scale movements best elucidated using complementary techniques.

Black Family Forest Owners in the Southeastern United States: A Case Study in Six Counties - Amanda Robillard; Cassandra Johnson Gaither; John Schelhas; Brett J Butler (Journal of Forestry, 2024)
The USDA Forest Service, National Woodland Owner Survey asks family forest owners (FFOs) about their attitudes and intentions regarding their forestland. Historically, the number of responses from Black or African American FFOs has been very low, but it is uncertain whether this is because of nonresponse bias or that there are relatively few Black FFOs. To get a better understanding of these FFOs and to test a method to increase response rates, an intensified survey effort was conducted in three southern states: Alabama, North Carolina, and South Carolina. Analyses indicate that Black FFOs have slightly different objectives, activities, and ownership structure for their forestland than their White counterparts, who have traditionally represented the majority of FFOs. Study Implications: By conducting an experiment to increase response rates from Black family forest owners to the National Woodland Owner Survey, we find traditional methodology is not effective. More importantly, we see this group has moderately different responses than their White counterparts. This has wide ranging implications for landowner assistance programs and other initiatives that have been designed on the premise that we are accurately capturing responses from all woodland owners.

Wildfire and Family Forest Owners: Concern, Advice, and Wildfire Reduction Behaviors from the United States National Woodland Owner Survey - Sarah M Butler; Brett J Butler; Emma M Sass (Forest Science, 2024)
Extreme wildfire is an increasing threat to lives, property, and ecosystems across the United States and many parts of the world. Family forest owners (FFOs) own a large percentage of forestland in the United States, and actions and behaviors on their forestland have a large impact on wildfire prevention and mitigation across the landscape. Using data from the USDA Forest Service’s 2018 National Woodland Owner Survey, we investigated national and regional FFO wildfire attitudes and behaviors. We see that concern for wildfire is relatively high across the United States; however, this concern does not always lead to wildfire reduction activities on the landscape. There is some variation among regions, with concern about wildfire and past wildfire reduction activities highest in the western US (76% and 37%, respectively), followed by the South (63% and 11%, respectively), and lowest in the northern region (50% and 8%, respectively). Understanding these aspects of wildfire and FFOs on a national level provides a broader context for the more focused studies across the country and acts as a launch point for more in-depth research in the future. Study Implications: This study assesses family forest owner (FFO) wildfire concern, information needs, and action, both past and intended, at national and regional levels across the United States. As wildfire is predicted to increase in frequency and severity into the future due to climate change, this research provides a reference line and a launch point for future studies. Understanding current concern levels and landowner characteristics can inform programs and policies aimed at mitigating severe wildfires. For example, the disconnect between concerns and actions can be used as an entry point for motivating additional owners to take steps towards active management. Concentrating efforts in fire-prone areas is important, but seeing that wildfire is a concern of family forest owners across much of the country suggests that this can be an important issue for starting conversations with many owners and possibly increasing their engagement with conservation efforts.

Distribution and dynamics of private forests across the United States - Marla Markowski-Lindsay; Brett J. Butler; Jesse Caputo; David Newman; Daowei Zhang; David Wear (Forest Policy and Economics, 2024)

Trends in United States Family Forest Owners’ Attitudes, Behaviors, and General Characteristics from 2006 to 2018 - Emma M Sass; Brett J Butler; Jesse Caputo; Emily S Huff (Forest Science, 2023)
Family forest owners (FFOs) control a plurality of forestland in the United States, and the decisions these landowners make have a profound impact on the landscape. Most research on FFOs consists of cross-sectional studies, although many of these recognize the importance of capturing long-term trends to understand whether and how FFO attitudes, behaviors, and general characteristics are changing. We use data from the 2006, 2013, and 2018 iterations of the USDA Forest Service, National Woodland Owner Survey (NWOS), with a bootstrapping approach to identify significant changes across these time periods among FFOs with 4+ hectares of forestland. Total FFO hectares decreased and FFO ownerships trended downward over the study period. A decreasing proportion of FFOs owned farms or homes near their forestland, harvested timber, or received advice. Demographic shifts include an increase in age and education level from 2006 to 2018, and an increase in FFOs of color from 2006 to 2013. Overall, we find a trend towards decreased traditional engagement and management and a slight increase in owning land for its amenity values. Understanding temporal trends in FFO characteristics, attitudes, and behaviors will help policymakers and forestry professionals inform and update their outreach, technical support, and financial assistance programs. Study Implications: Families and individuals hold more forestland than any other ownership group in the United States. We use nationwide survey data from 2006, 2013, and 2018 to determine whether and how these landowners are changing over time. The total forestland held by FFOs decreased between 2006 and 2018, and there has been a decrease in traditional forest management and engagement, such as through timber harvesting and nearby farm ownership. This study provides insights for policies, programs, and outreach and a foundation for future long-term comparisons of this group.

Wood Supply from Family Forests of the United States: Biophysical, Social, and Economic Factors - Brett J Butler; Emma M Sass (Forest Science, 2023)
Wood products are an essential provisioning ecosystem service with US forests providing nearly one-fifth of global wood supply. As of 2018, an estimated 46% of the annual wood harvested came from corporate forests, 42% came from family forests, and the remainder came from other private, public, and Tribal forests. The supply of wood from corporate forests is well described by traditional economic models, but the supply from family forests is much less well understood. This article combines data from three components of the USDA Forest Service’s Forest Inventory and Analysis program—plots, landowner surveys, and mill surveys—with other data to model the wood supply from family forests in the United States. Results are summarized in terms of bivariate relationships and a logistic regression model. The model results show that basal area, stand origin, forest type, having timber as an ownership objective, the amount of annual income derived from their forestland, proximity to a mill, management advice, and region are significantly associated with family forest timber harvesting. The results should be useful for forest industry analysts and others interested in understanding the current and potential future supply of wood from family forests. Study Implications: Family forests provide an estimated 42% of the annual timber harvested in the United States. It is important to understand the factors affecting their harvesting behaviors to design effective policies and programs to ensure a continual supply and sustainable management of this critical resource. This article shows that timber harvesting by family forest owners is influenced by a combination of biophysical, social, and economic factors, including basal area, stand origin, forest type, having timber as an ownership objective, the amount of annual income derived from their forestland, proximity to a mill, management advice, and region. These results suggest that programs aimed at increasing the area covered by planted stands, the area covered by softwood stands, and the number of owners receiving forest management advice may be particularly influential in maintaining and increasing the amount of wood harvested from family forests.

Forester and Logger Response to Emerald Ash Borer in Massachusetts and Vermont: A Secondary Disturbance - Marla Markowski-Lindsay; Paul Catanzaro; Amanda Robillard; Brett J Butler; David A Orwig; Anthony W D’Amato; Jonathan R Thompson; Danelle M Laflower; Meghan Graham MacLean; Malcolm Itter (Journal of Forestry, 2023)
Forester and logger responses to the invasive emerald ash borer (EAB) could substantially affect regions across the United States. We analyzed forester and logger responses to EAB in Massachusetts and Vermont, exploring characteristics associated with purposeful targeting of substantial ash properties; managing forests differently because of EAB; and regeneration goals. One-third of respondents increased timber sales on ash properties, motivated by ecological, not economic, impacts of EAB. Nearly 60% said EAB changed their management activity in stands with ash; changes influenced by the ecological impact of EAB and not economic factors. Those influenced by EAB’s ecological impact to choose properties with substantial ash were more likely to have increased harvest area size, sawtimber removal, and harvest intensity. Loggers were more likely than foresters to remove small-diameter ash and low-grade trees. Both rated regenerating economically valuable species well adapted to the site as their highest essential priority.

If A Tree Falls in A Forest, Why Do People Care? An Analysis of Private Family Forest Owners’ Reasons for Owning Forest in the United States National Woodland Owner Survey - David W. Shanafelt; Jesse Caputo; Jens Abildtrup; Brett J. Butler (Small-scale Forestry, 2023)

USDA Forest Service Timber Products Output Survey Item Nonresponse Analysis - Marla Markowski-Lindsay; Consuelo Brandeis; Brett J Butler (Forest Science, 2023)
The Timber Products Output (TPO) survey is used to determine industrial uses of roundwood, reporting on volumes of roundwood received and residues generated by the primary forest industry by tree species and counties of harvest. This knowledge aids stakeholders in making informed decisions about available forest resources and/or harvest intensity. The widespread use of TPO estimates makes it important to understand the scale and scope of missing data in the survey. This first attempt analyzed respondent-level and question-level nonresponse (RLNR and QLNR, respectively) for Northern and Southern TPO regions, comparing response to mill profile questions (those providing general business information) to those related to mill activity (that related to wood processing information). The RLNR differed between regions, by question grouping, survey mode, and mill volume. The QLNR results for selected mill activity questions indicate that the Southern region generally has lower nonresponse than the Northern region. Parametric analysis of RLNR indicated survey mode was significant for both question groups in the Northern region whereas mill type was significant for mill activity questions in the Southern region. The QLNR parametric analysis indicated self-administered surveys in the Northern region were associated with higher nonresponse, and surveys completed by sawmills in the Southern region were associated with lower nonresponse. Study Implications: Analysis of survey item nonresponse in the national Timber Products Output survey provides analytic background needed to assess the accuracy and completeness of the survey data. Population estimates from the data are used to monitor roundwood production and make informed decisions about forest resources. Responses varied across specific questions, and regional differences appeared to be related to survey mode. Current survey design could be improved to allow for analysis of all survey questions and assessment of the quality of responses. For nonresponse adjustment methods to be comparable across regions, factors causing observed regional difference should first be addressed.

Studies of Family Forest Owners in the USA: A Systematic Review of Literature from 2000 through 2019 - Brett J. Butler; Sarah M. Butler; Kristin Floress (Small-scale Forestry, 2023)

Phylogeography and taxonomy of Coleonyx elegans Gray 1845 (Squamata: Eublepharidae) in Mesoamerica: The Isthmus of Tehuantepec as an environmental barrier - Brett O. Butler; Lydia L. Smith; Oscar Flores-Villela (Molecular Phylogenetics and Evolution, 2023)

United States Family Forest Owners’ Awareness of and Participation in Carbon Sequestration Programs: Initial Findings from the USDA Forest Service National Woodland Owner Survey - Emma M Sass; Jesse Caputo; Brett J Butler (Forest Science, 2022)
Family forest owners (FFOs) hold a plurality of forestland in the United States, and programs and markets exist that compensate landowners for sequestering and storing increased carbon through extended rotations, improved forest management, and increased forest cover. We used USDA Forest Service National Woodland Owner Survey (NWOS) data from 2018 to estimate the number of ownerships and their associated acreage that are enrolled, that are familiar but not enrolled, and that are unfamiliar with these programs, as well as differences in attributes among these groups. As of 2018, less than 0.1% (SE < 0.1%) of FFOs are enrolled in carbon sequestration programs, and collectively they hold an estimated 400,000 ha (SE = 100,000). FFOs who are enrolled have larger holdings, are more likely to participate in other programs, and are more concerned about climate change, among other characteristics. Most FFO holdings are too small to be viable in traditional carbon programs, although new and evolving programs might enable smaller landholdings to be feasible to enroll. Knowing the characteristics of ownerships that are enrolled or aware of programs will allow for more informed design and implementation; future monitoring will be important to identify trends as these programs become more widespread.

Reply to Comment on Economic Contributions from Conserved Forests: Four Case Studies of the USDA Forest Service Forest Legacy Program - Helena Murray; Paul Catanzaro; Marla Markowski-Lindsay; Brett J Butler; Henry Eichman (Forest Science, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Economic Contributions from Conserved Forests: Four Case Studies of the USDA Forest Service Forest Legacy Program - Helena Murray; Paul Catanzaro; Marla Markowski-Lindsay; Brett J Butler; Henry Eichman (Forest Science, 2021)
Privately-owned forests provide important environmental, economic, and cultural benefits to the general public. Resulting impacts from landownership changes and conversion of working forests to other land uses threaten these benefits. The USDA Forest Service Forest Legacy Program (FLP) permanently protects threatened private forests that are of environmental, cultural, and economic importance to the greater public while keeping land ownership and forest management at the private or local level. FLP provides grants to state agencies to purchase conservation easements on private forestlands or, less frequently, acquisition by public agencies. We employed IMPLAN’s input-output model of the 2016 economy to estimate how land protected by FLP in four regions of the United States contributes to the economy. FLP land adds tens of millions of dollars of value annually and supports thousands of jobs in the four study areas and, due to the permanent protection of these lands, they will continue to do so in perpetuity. Nonfederal partners contributed 34%–60% of total project costs, highlighting the importance of land conservation to multiple stakeholders and the ability to leverage federal resources. The permanent nature of FLP protection provides long-term security for the economic and cultural benefits these lands provide.

Understanding the Spatial Pattern and Driving Factors Associated with Timberland Ownership Change in the Northern United States - Karun Pandit; Eddie Bevilacqua; David H Newman; Brett J Butler (Journal of Forestry, 2021)
This study analyzes changes in timberland ownership from 2003 to 2012 across the northern United States based on Forest Inventory and Analysis data identified according to five ownership categories. A total of 26,940 FIA plots that were remeasured between selected years were used for the analysis. Publicly available corporate ownership data were investigated and used to differentiate industrial and institutional (timber investment management organizations [TIMO] and real estate investment trusts [REIT]) ownership. Kernel density, Ripley’s K-function, and multinomial logistic regression (MLR) methods were used to study spatial patterns of timberland ownership and to explore statistical relationships. Among FIA plots showing ownership changes, the largest observed shift was from industrial to institutional ownership, with a 45% increase in the number of plots, equivalent to almost 1.4 million acres of timberland area. Bivariate Ripley’s K-function showed significant clustering for shifts between industrial and institutional ownership. A MLR model identified forest type as a significant factor associated with the transition of industrial timberlands to either institutional or family forest ownership. In addition, shifts from industrial to institutional ownership were related to road access and population density.

Dynamics of Large Corporate Forestland Ownerships in the United States - Emma M Sass; Marla Markowski-Lindsay; Brett J Butler; Jesse Caputo; Andrew Hartsell; Emily Huff; Amanda Robillard (Journal of Forestry, 2021)
Ownership of forestland in the United States has changed in recent decades, including the proliferation of timber investment management organizations (TIMOs) and real estate investment trusts (REITs), with the potential to alter forest management and timber supply. This article quantifies forest ownership transitions among ownership categories between 2007 and 2017 and investigates how and why large corporate ownerships own and manage their forestlands. Ownership transitions were determined from refined USDA Forest Service, Forest Inventory and Analysis data; we also conducted a survey of large corporate forestland ownerships. Corporate forestland acreage increased between 2007 and 2017, while family and public forestland decreased. Large corporate landowners report multidimensional, financially focused land management, although industry, timber investment management organizations, real estate investment trusts, and other owners report some different motivations and income streams. This work provides a baseline to track future ownership transitions and the behaviors of large corporate forestland owners.

One Size Does Not Fit All: Relationships between Size of Family Forest Holdings and Owner Attitudes and Behaviors - Brett J Butler; Jesse Caputo; Amanda L Robillard; Emma M Sass; Chris Sutherland (Journal of Forestry, 2021)
An estimated 10 million families, individuals, trusts, and estates own 39 percent of the forestland in the United States, excluding interior Alaska. Using segmented regression, the relationships between size of forest holdings and the attitudes and behaviors of these family forest ownerships were tested using data from the 2018 iteration of the USDA Forest Service’s National Woodland Owner Survey. All 16 variables tested have significant relationships with size of forest holdings, and 13 have one or more breakpoints, ranging from 40 to 5,854 ac, where the relationships between the variables change. Timber as a reason for owning, timber harvesting activities, management plan, advice received, land certified, tax program participation, cost share, recreation, land tenure, recreation, taxes and heirs as concerns, land transfer, and income from forestland have positive relationships with size of forest holdings; resident ownership has a negative relationship; and wildlife as a reason for owning and owner age have mixed relationships.

Transformations Towards a New Era in Small Scale Forestry: Introduction to the Small-Scale Forestry Special Issue - Teppo Hujala; Brett J. Butler (Small-scale Forestry, 2020)

The “Coming Age of Wood” and Family Forest Owners: An Implications Wheel® Exploration - David N. Bengston; Teppo Hujala; Brett J. Butler (Small-scale Forestry, 2020)

Minority Family Forest Owners in the United States - Sarah M Butler; John Schelhas; Brett J Butler (Journal of Forestry, 2020)
Family forest owners own more forestland in the United States than any other group. There have been no national studies of racial and ethnic minority family forest owners in the United States, in spite of increasing attention to diversity in forestry. Using the US Forest Service’s National Woodland Owner Survey data, we sought to better understand minority owners by looking at their characteristics, attitudes, and behaviors. Of the over 4 million family forest ownerships with 10+ ac in the United States, minorities comprise 6.6 percent of the ownerships and own 5.1 percent of the 265 million ac. Although many similarities exist between minority and nonminority owners, such as reasons for owning land and concerns, minority landowners tend to be more regionally located, have smaller forest holdings, are less likely to manage their forests, and are less likely to have participated in assistance programs. Broad insight into the attitudes and behaviors of minority family forest owners can help policymakers, program directors, and outreach coordinators begin to understand the needs of minority landowners, providing this historically underserved group with tools they need to attain their forest management and land-use goals. By increasing minority landowner engagement, we can hopefully slow the loss of land by minority landowners.

Small-Area Family Forest Ownerships in the USA - Stephanie A. Snyder; Brett J. Butler; Marla Markowski-Lindsay (Small-scale Forestry, 2019)

In Forest and Intact: Designating Future Use of Family-Forest-Owned Land - Marla Markowski-Lindsay; Paul Catanzaro; Kathleen Bell; David Kittredge; Ezra Markowitz; Jessica Leahy; Brett Butler; Anita Milman; Shorna Allred (Journal of Forestry, 2018)

Isotope ( δ 13 C, δ 15 N, δ 2 H) diet–tissue discrimination in African grey parrot Psittacus erithacus : implications for forensic studies - Craig Symes; Felix Skhosana; Mike Butler; Brett Gardner; Stephan Woodborne (Isotopes in Environmental and Health Studies, 2017)

Methods for Increasing Cooperation Rates for Surveys of Family Forest Owners - Brett J. Butler; Jaketon H. Hewes; Mary L. Tyrrell; Sarah M. Butler (Small-scale Forestry, 2017)

Family Forest Owner Characteristics Shaped by Life Cycle, Cohort, and Period Effects - Sarah M. Butler; Brett J. Butler; Marla Markowski-Lindsay (Small-scale Forestry, 2017)

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Family Forest Owners’ Perceptions of Landowner Assistance Programs in the USA: A Qualitative Exploration of Program Impacts on Behaviour - Kyle Andrejczyk; Brett J. Butler; Brenton J. Dickinson; Jaketon H. Hewes; Marla Markowski-Lindsay; David B. Kittredge; Michael A. Kilgore; Stephanie A. Snyder; Paul F. Catanzaro (Small-scale Forestry, 2016)

Aborigine‐managed forest, savanna and grassland: biome switching in montane eastern Australia - Don W. Butler; Roderick J. Fensham; Brett P. Murphy; Simon G. Haberle; Sarah J. Bury; David M. J. S. Bowman (Journal of Biogeography, 2014)
Aim To assess hypotheses about the role of anthropogenic fire in the maintenance and origin of a fine‐scale vegetation mosaic of rain forest, eucalypt savanna and grassland. Location Bunya Mountains, subtropical eastern Australia. Methods A time series of vegetation maps was compiled from historical and recent aerial photography and field surveys. Geospatial models were constructed of environmental domains for rain forest, savanna and grassland, and for areas of biome change. Grassland soils were analysed for carbon isotope ratios (δ 13 C), and radiocarbon ( 14 C) dates were acquired for bulk samples from a range of depths. Results Analysis revealed weak associations between topography and the distribution of rain forest, savanna and grassland, and their patterns of recent change. Grassland occupied an environmental domain intermediate between rain forest and savanna and was more than four times as likely to occur within a matrix of rain forest rather than savanna. There was a large proportional reduction in the area of both grassland (−35%) and savanna (−19%) between 1961 and 2006 because of the expansion of rain forest. However, the greater initial extent of savanna meant that the areal loss of savanna was an order of magnitude greater than for grassland (1433 vs. 146 ha). There was no evidence of abrupt changes in δ 13 C in grassland soil profiles, indicating stability of the vegetation over the last 2000 years. Main conclusions There is no simple gradient in ‘tree suitability’ from rain forest, through savanna, to treeless grassland on the Bunya Mountains. A general absence of fire since the 19th century has greatly reduced the extent of grassy savanna and grassland formations, to the advantage of rain forest. These results support the hypothesis that the vegetation mosaic on the Bunya Mountains is a cultural artefact and testament to millennia of skilful and persistent burning. We could not conclusively reject the hypothesis that the grasslands are Pleistocene relicts that have declined throughout the Holocene; nonetheless, an explanation more consistent with the evidence overall is that the grasslands must have had periods of expansion during the Holocene, probably as a consequence of severe fires that have destroyed patches of rain forest.

Methods for Estimating Private Forest Ownership Statistics: Revised Methods for the USDA Forest Service's National Woodland Owner Survey - Brenton J. Dickinson; Brett J. Butler (Journal of Forestry, 2013)

Consulting Forestry / Certification and Ecosystem Services - James Coufal; Carl Wiedemann; Jacob Gorman; Larry Teeter; Yaoqi Zhang; Michael Kilgore; Kristell Miller; Stephanie Snyder; Sun Chang; Miriam Davis; Stanley Asah; J. Mark Fly; et al. (Journal of Forestry, 2011)
45The industrialization of the United States throughout the 19th century resulted in the exploitation of millions of acres of timberland across the country. Logging during that era was described by critics as “cut out and get out” because the land was usually abandoned after the merchantable timber was exhausted. Concern about future timber supplies and the effect of logging on watersheds spurred the development of professional forestry after the Civil War. The first forestry leaders, including Bernhard Fernow and Gifford Pinchot, encouraged private non-industrial forest owners to sustainably manage their woodlands and specifically warned against destructive logging practices—including “cutting the best and leaving the rest”—aka high-grading. During the 1920s and 30s both the Forest Service and SAF spurred initiatives to encourage sustainable timber harvesting practices on private forestland. Although great progress has been made in forest management, logging on most private non-industrial forest land in the east has not changed significantly since the 19th century. Landowners usually sell timber without using the services of a forester, allowing the buyer to selectively cut the most valuable trees in the woodlot. Although this can reduce future value by 70-90%, it remains common practice because both the landowner and the timber buyer maximize short term income. The timber value and productivity of millions of acres of woodland throughout the United States have been significantly degraded as a result. This paper will trace the history of high-grading as described by forestry leaders from the 19th century through the 21st and will show that much work remains unfinished.

Forest Policy / Biosecurity - Linda Heath; Clark Row; Robert Perschel; Douglas Boucher; Patricia Elias; Katherine Lininger; Calen May-Tobin; Earl Saxon; Steven Ruddell; Sally Collins; Sarah Ruddell; Mo Zhou; et al. (Journal of Forestry, 2011)
7Massive fires in Indonesian peatlands in the 1990s and in eastern Russian peatlands in 2002 and last year have highlighted the need to manage forests overlying peat deposits, as well as converted peat forests and open peatlands. Peat or peaty soils, contain 65% or more of partially decayed vegetation, can burn freely or underground. They cover some 10 percent of worldwide forests and contain 25 percent of all terrestrial carbon. Recent massive greenhouse gas (GHG) emissions from fires in forested peat and peatland in Indonesia and in Russia highlight the need for policies to reduce GHG emissions. We discuss major peatland areas and quantify their carbon stocks and potential GHG emissions. Trends show that year-to-year emissions are variable, with huge pulses that are a significant share of global GHG emissions. We group suggested policy options into three approaches. The first approach, which will reduce peat-related product demand, includes a) restricting peat, and products produced on cleared forested peatland, from being labeled or counted in GHG reduction achievements, as renewable (which palm oil currently is considered); b) developing full substitutes for horticultural peat (comprising about half mined peat use); and c) developing renewable power in countries still dependent on peat for power generation. These options reduce the rate of developing newly mined peat/forest areas. Options for a second approach, which treat already drained and cleared forested peatlands, are: d) restoring functioning peat ecosystems by closing drainage ditches, allowing natural rewetting, and “seeding” with peat vegetation fragments, e) requiring current peat operators to restore mined areas right after all peat is removed, and f) converting them to other land uses, despite the acidic conditions of mined peat bogs. These options sharply reduce risks of peat fires. Finally, a third group of policy options reduces ignition risks and limit fire spread: g) developing monitoring, suppression techniques, h) organizing local landowner protection groups and i) improving public fire organizations.

The Diverse Values and Motivations of Family Forest Owners in the United States: An Analysis of an Open-ended Question in the National Woodland Owner Survey - David N. Bengston; Stanley T. Asah; Brett J. Butler (Small-scale Forestry, 2011)

Relationships Between Major Ownerships, Forest Aboveground Biomass Distributions, and Landscape Dynamics in the New England Region of USA - Daolan Zheng; Linda S. Heath; Mark J. Ducey; Brett Butler (Environmental Management, 2010)

Motivations and Land-Use Intentions of Nonindustrial Private Forest Landowners: Comparing Inheritors to Noninheritors - Indrajit Majumdar; David Laband; Lawrence Teeter; Brett Butler (Forest Science, 2009)
The documented importance of intergenerational human capital transfers in agriculture generally gives us reason to suspect that such transfers may be important in a forestry context and that there may be important implied differences between first-generation woodland owners and multigeneration woodland owners with respect to their motivations and future intentions. In turn, knowledge of the motivations and intentions of nonindustrial private landowners may be extremely important because such knowledge may be vital in terms of our ability to predict future timber supply and the availability of nontimber amenities. Also, the effectiveness of public policies targeting nonindustrial private forest landowners may depend critically on their motivations and intentions. In this article, we analyzed 8,373 responses to the National Woodland Owner Survey to compare characteristics, motivations, and intentions of multigeneration forest landowners against those of single-generation forest landowners. In brief, we found there were significant differences in their motivations and management behavior; inheritors are more active forest managers and manage for both timber and nontimber forest products more aggressively than noninheritors who typically value esthetics, privacy, protection of biodiversity, and nonhunting recreation.

Farmers’ objectives toward their woodlands in the upper Midwest of the United States: implications for woodland volumes and diversity - W. Keith Moser; Earl C. Leatherberry; Mark H. Hansen; Brett J. Butler (Agroforestry Systems, 2009)

Characterizing Family Forest Owners: A Cluster Analysis Approach - Indrajit Majumdar; Lawrence Teeter; Brett Butler (Forest Science, 2008)
For policy implementation to promote better stewardship on family forestlands, it is necessary to understand what motivates landowners. This study characterizes family forest owners in Alabama, Georgia, and South Carolina, based on their feelings about forest stewardship and their stated reasons for owning forestland. Multivariate cluster analysis suggests that family forest owners are, in fact, a diverse set of owners who can be grouped into three attitudinal types, namely, multiple-objective, nontimber, and timber. The multiple-objective ownership type was found to be the largest group (49.1% of respondents) with almost half the family forest owners in the sample population belonging to this category. Owners belonging to the timber cluster (29.4%) indicated only timber management and land investment as strong motivating factors behind their forestland ownership, whereas owners belonging to the nontimber cluster (21.5%) value the nonconsumptive uses of their forestland such as aesthetic values, biodiversity, recreation, and privacy.

Understanding and Reaching Family Forest Owners: Lessons from Social Marketing Research - Brett J. Butler; Mary Tyrrell; Geoff Feinberg; Scott VanManen; Larry Wiseman; Scott Wallinger (Journal of Forestry, 2007)
Social marketing—the use of commercial marketing techniques to effect positive social change—is a promising means by which to develop more effective and efficient outreach, policies, and services for family forest owners. A hierarchical, multivariate analysis based on landowners' attitudes reveals four groups of owners to whom programs can be tailored: woodland retreat, working the land, supplemental income, and ready to sell. A prime prospect analysis segmenting landowners according to their level of engagement and interest in land management can be used to improve the efficiency of program implementation. Landowners showing low levels of engagement but high levels of interest are of special interest because they are likely to be receptive to a social marketing message and therefore should be a priority target for any such efforts. Using the demographic profile of the average family forest owner, newspapers and television were identified as important means for mass communication.

America's Family Forest Owners - Brett J. Butler; Earl C. Leatherberry (Journal of Forestry, 2004)
The number of family forest owners in the conterminous United States increased from 9.3 million in 1993 to 10.3 million in 2003, and these owners now control 42% of the nation's forestland. The reasons why people own forestland are diverse. Some of the more common ones are aesthetic enjoyment, the tract is part of a farm or home site, and to pass the land on to heirs. Half of the family forest owners have harvested trees, but only 3% of them have a written forest-management plan. Trends in owners' ages and future land-use intentions suggest widescale transfers of family forestland in the near future.

Projecting Large-Scale Area Changes in Land Use and Land Cover for Terrestrial Carbon Analyses - Ralph J. Alig; Brett J. Butler (Environmental Management, 2004)